Perbandingan Pemeriksaan Toksigenisitas secara Genotip dan Fenotip pada Beberapa Isolat Corynebacterium diphtheriae Penyebab Difteri di Indonesia - Sunarno, Sunarno; Sariadji, Kambang (Puslitbang Biomedis dan Teknologi Dasar Kesehatan, 2016)
Corynebacterium diphteriaeâs toxin can be detected by using in vivo and in vitro examination. Detection of the toxin using the guinea pig is a gold standard. This method requires a long time and has been opposed by animal right organization. There is another alternative method such as vero cell cytotoxicity and Elek test. The limitation of these methods are reagent procurements, technical skill, and a long processing time. Other alternative method like polymerase chain reaction (PCR) can overcome the limitation. PCR can detect the toxin quickly and the results can be interpreted easily. Some previous study showed there was the difference results between PCR and Elek test or vero cell cytotoxicity. The Aim of this study is to compare genotypic toxin detection using PCR and phenotypic detection using Elek test, on some isolates that caused diphtheria outbreak in Indonesia. A total of 12 isolates have been tested in this study. These isolates were obtained from the outbreak cases in Indonesia and isolated in Bacteriology Laboratory, Center for Research and Development of Biomedical and Basic Technology of Health. This study used reference strains as positive and negative controls (NCTC 10648, NCTC 3984 and NCTC 10356). All samples were examined by PCR for toxin genotyping detection, and Elek test for phenotyping detection. The results showed as many as 10 isolates were toxigenic C. diphtheriae while the remaining were non-toxigenic. There was no nontoxigenic tox-gene bearing (NTTB). There were no difference results between PCR and Elek test to detect the toxin.Â Â Â Â Â Â Â Â Â Base on the results of this study, there was a 100% conformity results between PCR and Elek test to detect the toxin of C. diphteriae.